2013
DOI: 10.1063/1.4829632
|View full text |Cite
|
Sign up to set email alerts
|

Shock-induced termination of reentrant cardiac arrhythmias: Comparing monophasic and biphasic shock protocols

Abstract: In this article, we compare quantitatively the efficiency of three different protocols commonly used in commercial defibrillators. These are based on monophasic and both symmetric and asymmetric biphasic shocks. A numerical one-dimensional model of cardiac tissue using the bidomain formulation is used in order to test the different protocols. In particular, we performed a total of 4.8 Â 10 6 simulations by varying shock waveform, shock energy, initial conditions, and heterogeneity in internal electrical conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 41 publications
(44 reference statements)
4
13
0
1
Order By: Relevance
“…4. This is in line with earlier findings 39 . On the other hand, the defibrillation success is almost unaffected by the boundary conditions.…”
Section: B Single Pulse Defibrillationsupporting
confidence: 83%
See 1 more Smart Citation
“…4. This is in line with earlier findings 39 . On the other hand, the defibrillation success is almost unaffected by the boundary conditions.…”
Section: B Single Pulse Defibrillationsupporting
confidence: 83%
“…We fixed the total pulse duration to 10 ms and optimized the ratio of forward to backward duration. For fixed parameters, we found that 7 ms (forward) and 3 ms (backward) leads to best defibrillation results, in agreement with 38,39 , where the best efficiency is obtained when the first phase is about twice as long as the second phase. Our low-energy antifibrillation pacing (LEAP) protocol contains n identical biphasic pulses, where the interval T between two pulses is constant and defined between the onsets of neighboring pulses.…”
Section: Defibrillation Protocolssupporting
confidence: 73%
“…This simplification was exploited in a seminal work by Glass and Josephson [13] in the 1990s, in which a one dimensional geometry was used to study the annihilation and the resetting of reentrant waves. This original study was further broadened by the inclusion of conductivity heterogeneities and multiple stimuli [12,[14][15][16][17][18].…”
Section: Model and Methodsmentioning
confidence: 99%
“…In this study [12], it was shown that the threshold E 50 , the applied electric field corresponding to a 50% of probability of success for defibrillation shocks, is achieved mainly by front to front interactions or interactions of the front with the refractory tissue, while the threshold E 90 needed for a 90% of probability of success is mainly obtained through a different mechanism, consisting of a direct activation of the whole cardiac tissue. Examining the mechanisms for defibrillation at low energy (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation